High Accuracy Buoyancy for Underwater Gliders: The Uncertainty in the Depth Control - Enrico Petritoli; Fabio Leccese; Marco Cagnetti (Sensors, 2019)
This paper is a section of several preliminary studies of the Underwater Drones Group of the Università degli Studi “Roma Tre„ Science Department: We describe the study philosophy, the theoretical technological considerations for sizing and the development of a technological demonstrator of a high accuracy buoyancy and depth control. We develop the main requirements and the boundary conditions that design the buoyancy system and develop the mathematical conditions that define the main parameters.